Metal-organic framework membranes with single-atomic centers for photocatalytic CO2 and O2 reduction - Yu-Chen Hao (Nature Portfolio, 2021)
Photoreduction of permanent gas faces challenges in reactant diffusion and activation at the three-phase interface. Here the authors showed porous metal-organic framework membranes decorated by metal single atoms can boost the photoreduction of CO2 and O2 at the high-throughput gas-solid interface.